If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-35/5=X/5-7
We move all terms to the left:
X-35/5-(X/5-7)=0
We add all the numbers together, and all the variables
X-(X/5-7)-7=0
We get rid of parentheses
X-X/5+7-7=0
We multiply all the terms by the denominator
X*5-X+7*5-7*5=0
We add all the numbers together, and all the variables
-1X+X*5=0
Wy multiply elements
-1X+5X=0
We add all the numbers together, and all the variables
4X=0
X=0/4
X=0
| 14+(9•8)×t=0 | | (6p+16)=7.5 | | 20(1,05^x)=30 | | 12-3(2-x)=0 | | 20*1,05^x=30 | | 36x^2+36x+9=729 | | 2k-3k(2k-3)=45 | | 5y—11=7y±13 | | 24-6b=3(-2b+8) | | 2b=17+7 | | 15y^2-41y+12=0 | | 4m-5(3m+10)=124 | | 3-d=3+8-3d(3) | | 3/(2m+4)=(1/(m+2))-2 | | x/3-x/3=0 | | x-34=-22 | | 6x-8x/2=-x | | -11x+5=5-11x | | 13x+9/7=5 | | x/4+x/4=x/2 | | 4(m+7)+5(m+4)=-6 | | 5(4x+6)-5(-6x-8)=20 | | -8-2/3hh=6 | | x+4x=8x-3x-1 | | x^2+2.4x+4=0 | | 16+x=6x-2-2x | | |2x|-8=10 | | V-7=-15+2v | | 7m+6÷3-4m+2÷4=2m+1÷3-2 | | -2.5(4g-8)=0.5(4-2g) | | 2(2+7x)=83 | | 8x+3=5x-5 |